Workplace ethics: the opposition of standards at workplace / Nur Amirah Ayub Khan ... [et al.] - Ayub Khan, Nur Amirah; Salleh, Ainal Maziah; Abd Rahman, Amir Lukman; Ahyat, Muna Munirah (Universiti Teknologi MARA Shah Alam, 2018)
This study explains thoroughly in workplace ethical issues as these issues have been a controversial issue in organisations. Thus, this study will explore reviews related to literature in terms of two significant issues of employee theft and the abuse of official working hours. This study contributes a combination of a few terms, but it centres more in getting a better understanding in the factors that influence these significant issues regarding the ethical standards at a workplace with the help of comprehensive strategies in getting data. This paper specifies "workplace ethics" as one of the advantages in helping organisations to remain a good reputation and increase work productivity